The First Online Semester in the Perspective of Students and Profesors - Mihailova, Katia; Mirchev, Mihail (Research Papers, 2021)
COVID-19 forced our first attempt at university online learning as an anti-crisis measure during the state of emergency (13 March – 13 May 2020). In this period, we conducted two empirical researches of student and faculty reflection on online education at UNWE. The first one reflects the initial impressions of students and teachers of this new form of education, registered in the second week of the online semester (15 – 22 March 2020). The second examines the quality of online learning and attitudes towards the first online session (5 – 15 June 2020). The primary information is collected through an online survey with original questionnaires, developed for the purposes of research. The respondents in the first survey are approximately 9%, and in the second – 19% of the students at UNWE in 2019 – 2020. The samples do not claim to be representative and valid for the students at UNWE as a whole. The results are valid only for UNWE active students who regularly attend lectures, including online lectures, as well as for online active professors from UNWE. The research data and results are presented in the paper. We can say that the research from March 2020 is the first Bulgarian survey in the field of online higher education with original methodological tools. Together with the second from June 2020, they cover the first online semester and session in their inseparable connection.